Exploration and Utilization of Plant Species Based on Social Culture (Hindu Religion Ceremony) in Tenganan Pegringingan Village, Karangasem Regency, Bali Province, Indonesia - Wijana, Nyoman; Mulyadiharja, Sanusi; Riawan, I Made Oka (International Journal of Natural Science and Engineering, 2020)
This research aims to find out (1) the plants that were used in religious ceremonies (Hinduism) in accordance with the Bali Aga Tenganan Pegringsingan culture. 2) the making process of the various means needed in religious ceremonies (Hinduism) related to the utilization of useful plant species in Bukit Kangin Forest, Tenganan Pegringsingan Village. The Research was explorative (vegetation) and socio-system (community) research. The populations of this research were ecosystem aspects and sociosystem aspects. The ecosystem aspects included all of the useful plant species in Bukit Kangin Forest of Tenganan Pegringsingan village. Meawhile, the sociosystem aspects included the village officials, the village public figures and the community of Tenganan Pegringsingan village. The ecosystem sample (the vegetation) used in this research included the plant species in the forest of Tenganan Pegringsingan Village covered by the 1x1m2 sized seedling square, 10x10m2 sized sapling square and 20x20m2 sized square for trees (mature plants). There were 65 squares in total. The sociosystem samples in this research were the village officials, public figures, shamans, offerers, craftsmen, and the public in Tenganan Pegringsingan village. The methods applied in this research were (1) square method for ecosystem (vegetation) parameter. (2) Interview, questionnaire and observation for sociosystem parameter. The collected data were further analyzed descriptively. The results of the research showed that (1) of 46 useful plant species found in Bukit Kangin forest of Tenganan Pegringsingan, 29 of them were plant species that were utilized for religious ceremonies (Hinduism), meanwhile there were 17 plant species utilized for clothing, food, shelter, industry, medicine, and other household purposes. (2) The utilization of plant species for religious purposes was still in traditional method, in accordance with the socio-cultural of the local community.